Religious Tolerance as a Lived Experience: A Phenomenological Study of Adolescents' Interfaith Engagement in Rural Indonesia - Taufik Hidayat Almedy (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2025)
This study examines how adolescents in Kalurahan Watusigar, a village in Yogyakarta, Indonesia known for its longstanding religious diversity, understand and practice religious tolerance in their daily lives. In this community, Muslims, Christians, and adherents of other faiths have coexisted for generations, making it a significant setting to explore interfaith experiences among adolescents in a rural plural context. Using a phenomenological approach with Interpretative Phenomenological Analysis (IPA), semi-structured interviews were conducted with three adolescents aged 15–18 who actively engage in interfaith interactions. The analysis identified six superordinate themes: (1) diversity as a lived social reality, (2) tolerance and appreciation of differences as core values, (3) religious freedom as a personal right, (4) positive interfaith social interaction, (5) cultural participation and empathy toward other traditions, and (6) collaboration across religious boundaries. A unique theme highlighted the affective and participatory dimension of tolerance. The findings demonstrate that in Watusigar, adolescent religious tolerance is not merely a normative ideal but an embodied and internalized social practice. By situating the lived experiences of youth within a plural rural setting, this study contributes to global discussions on adolescence, interfaith engagement, and peacebuilding. It also underscores the significance of character education grounded in religious moderation for fostering inclusive and harmonious interfaith relations.